From shear exfoliation of graphite in Coca-Cola® to few-layer graphene for smart ink - Ismail, Zulhelmi; W. Idris, Wan Farhana; Abdullah, Abu Hannifa (Elsevier, 2021)
Liquid-phase exfoliation of few-layer graphene in Coca-Cola ® was performed by a kitchen blender for rapid preparation of strain/light/humidity sensitive ink. The advantages of Coca-Cola as an exfoliating medium have been identified from the low structural defect (ID/IG = 0.39) and, moderate carbon to oxygen ratio (C/O = 2.6) obtained by the resulting graphene. It is discovered that a deposition of graphene on photo paper allowed a facile fabrication of smart paper that is able to detect minor strain (0 – 2.0%) with GF of 18.7. Meanwhile, the multi-responsiveness of ink towards light/humidity had been validated from the 10 s response time after the exposure to stimulants with the maximum resulting curvature degree of 16° and 14° under light and humidity changes, respectively. Finally, it is shown that our actuator is able to vertically lift a load (545 mg) from its initial flat position upon irradiation of light (200 mW/cm2).